Newspaper Editorial Policy in Determining the Appearance of The Main Page (Case Study of Pos Kota Daily) - Devi Ula Sartika (International Journal of Social Sciences Review, 2020)
The research subject, Pos Kota Daily, is a print media in West Jakarta. The method used in this research is a case study with a descriptive qualitative approach. The data collection process used was direct interview, observation and documentation study. The subject of the research is Pos Kota Daily which is a print media located in West Jakarta. The method used is a case study with the type used is descriptive qualitative. The data collection process used was direct interview, observation and documentation study. The selection of informants is based on the duties, responsibilities and authority of the informants. The theory used is the theory of Media Ecology. The results of the research process of the Pos Kota editorial policy, namely Pos Kota, are consistent with the news content presented, such as the news delivered coming from human interest issues from local to national issues. The non-standard use of the Indonesian language in the contents of the headline and headlines in the appearance is made briefly, clearly and clearly, so that it can be accessed by readers. The scope of news restriction is around law and crime, urban, national, sports, social culture. Providing actual, informative news and the function of media information, aspirations and entertainment have been done by Pos Kota. Changes made by Pos Kota were seen in the logo, paper size and the number of stories reduced to 13 stories and the appearance of caricatures that were considered sweeteners. Based on the three factors in Media Ecology theory, the Pos Kota editors pay attention to content, readerparticipation and advertising revenue as a way to survive facing the Pos Kota newspaper.